A Unified Model of Cohort Mortality for Economic Analysis. (IMF Working Papers; Working Paper ;, 2021)
We propose a dynamic production function of population health and mortality from birth onwards. Our parsimonious model provides an excellent fit for the mortality and survival curves for both primate and human populations since 1816. The model sheds light on the dynamics behind many phenomena documented in the literature, including (i) the existence and evolution of mortality gradients across socio-economic statuses, (ii) non-monotonic dynamic effects of in-utero shocks, (iii) persistent or 'scarring' effects of wars and (iv) mortality displacement after large temporary shocks such as extreme weather.